2018
DOI: 10.1371/journal.pone.0203020
|View full text |Cite
|
Sign up to set email alerts
|

The structure-function analysis of the Mpr1 metalloprotease determinants of activity during migration of fungal cells across the blood-brain barrier

Abstract: Cryptococcal meningoencephalitis, the most common form of cryptococcosis, is caused by the opportunistic fungal pathogen, Cryptococcus neoformans. Molecular strategies used by C. neoformans to invade the central nervous system (CNS) have been the focus of several studies. Recently, the role of a novel secreted metalloprotease (Mpr1) in the pathogenicity of C. neoformans was confirmed by studies demonstrating that Mpr1 mediated the migration of fungal cells into the CNS. Given this central function, the aim her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…Strikingly, the sole expression of cryptococcal MPR1 in S. cerevisiae endowed the yeast cells with the ability to cross the BBB, which demonstrated that Mpr1 is specific in breaching the BBB and suggested that Mpr1 may function independently of the hyaluronic acid-CD44 pathway in breaching the brain endothelium [88]. Further structure-function analysis of Mpr1 showed that both mutations in the cleavage sites of the prodomain and amino acid substitutions in the HExxH motif resulted in the failure of cryptococci to cross the BBB [91]. The proteolytic activity assay showed that the implementation of Mpr1 s complete function was dependent on the coordination of zinc with the HExxH motif in the active site of Mpr1 [91].…”
Section: Znfs Mediate Cryptococcusmentioning
confidence: 99%
See 1 more Smart Citation
“…Strikingly, the sole expression of cryptococcal MPR1 in S. cerevisiae endowed the yeast cells with the ability to cross the BBB, which demonstrated that Mpr1 is specific in breaching the BBB and suggested that Mpr1 may function independently of the hyaluronic acid-CD44 pathway in breaching the brain endothelium [88]. Further structure-function analysis of Mpr1 showed that both mutations in the cleavage sites of the prodomain and amino acid substitutions in the HExxH motif resulted in the failure of cryptococci to cross the BBB [91]. The proteolytic activity assay showed that the implementation of Mpr1 s complete function was dependent on the coordination of zinc with the HExxH motif in the active site of Mpr1 [91].…”
Section: Znfs Mediate Cryptococcusmentioning
confidence: 99%
“…Further structure-function analysis of Mpr1 showed that both mutations in the cleavage sites of the prodomain and amino acid substitutions in the HExxH motif resulted in the failure of cryptococci to cross the BBB [91]. The proteolytic activity assay showed that the implementation of Mpr1 s complete function was dependent on the coordination of zinc with the HExxH motif in the active site of Mpr1 [91].…”
Section: Znfs Mediate Cryptococcusmentioning
confidence: 99%
“…Mpr1 is sufficient for crossing in vitro blood brain barrier models. Expression of cryptococcal MPR1 in Saccharomyces cerevisiae allowed the species to cross an in vitro blood brain model, when it is normally incapable of doing so [392,393]. Mpr1 may facilitate transversal of the blood-brain barrier by stimulating cytoskeletal reorganization through interactions with Annexin A2 [393].…”
Section: Secreted Immunomodulatory Factorsmentioning
confidence: 99%
“…Previous studies demonstrated that Mpr1 is not required for fungal viability/growth, but rather, it functions as a major virulence factor by promoting Cn across the BBB (23,32,33). We propose that Mpr1 is a high-value target based on studies that found significantly less brain fungal burden in mice that had been inoculated with a strain of Cn lacking Mpr1 (32).…”
mentioning
confidence: 91%
“…In the case of Cn, only one M36 fungalysin, MPR1, is present in its genome (31,32). These secreted metalloproteases have a similar overall structure consisting of a signal peptide, a prodomain, and a catalytic domain that coordinates zinc and H 2 O for activity (33). So far, evidence for these metalloproteases support a role in fungal pathogenesis, but in most cases, their targets have not been identified (25).…”
mentioning
confidence: 99%